Unveiling the uncommon autoimmune insights: systemic lupus erythematosus and Addison’s disease - Khandait, Vinod; Kotwal, Aakash; Rathi, Tejas; Ruke, Mayur; Rathod, Joshna; Wazade, Aniket; Thakre, Gulshan (International Journal of Research in Medical Sciences, 2024)
Systemic lupus erythematosus (SLE) has been on the rise with the availability of easily accessible diagnostic modalities and prompt treatment. This autoimmune disease encompasses a wide range of clinical features, hinting at multisystem involvement. SLE manifesting as adrenal insufficiency has been reported in the literature as a rare occurrence. We describe one such uncommon case of an 18-year-old girl who presented with adrenal crisis. The clinical complexity of her presentation led to a comprehensive clinical and laboratory evaluation. An ANA-immunoblot revealed the underlying causative factor, SLE. She was started on parenteral therapy with steroids and showed a remarkable recovery. This case emphasizes the diverse presentations of SLE and the need to maintain a high index of suspicion when dealing with such peculiar cases. Early diagnosis and quick initiation of therapy are crucial in managing SLE effectively. Increased awareness among healthcare professionals is also essential to improve patient outcomes. This case highlights the importance of considering SLE in differential diagnoses, even in uncommon presentations, to ensure timely and appropriate treatment. With improved diagnostic capabilities, more cases like this can be identified and managed successfully.